“Bora agitar?!” : as crianças na Dança dos Mascarados de Poconé-MT - Queiroz, Poliana Jacqueline Oliveira (2016)
In the midwestern of Brazil, about one hundred kilometers away from Cuiabá, the capital city of Mato Grosso, there is a small town around 233 years old of existence. Pocone is the gateway to the Pantanal. Within this quiet town, there is a group composed of men of all ages who adorn themselves with colorful silk clothing, embroidered with sequins and wear mirrored hats. Dressed in this odd fashion, they embody beautiful ladies and courageous heartthrobs, and in pairs, they perform the “Dança dos Mascarados”, which translates The Dance of the Masquerades. This paper relied on dissertations about festivals and popular culture (Cavalcanti, 2001; Carvalho, 2010; Osorio, 2012; Perez, 2012) and those undertaken under the so called, infant anthropology (Cohn, 2005; Pires, 2010), which are the academic reports on the inclusion of the child on popular festivities. Its main object of study, is the Dance of the Masquerades Juvenile Group in the town of Poconé, in the state of Mato Grosso, Brazil. These children and adolescents are present in every group presentation and they replay the festivity spirit performing in the town and in its surroundings cities. By means of the participative observation method and trough the analysis of drawings and essays produced by the children, this study intended to discover the essence and meaning of the festival from the children's perspectives. The survey also sought to seek the link between the expressions of popular culture and the active participation of children in these festivities. With that in mind, the acts of celebrating and dancing appears as instruments of valuable learnings, which are guided by the teaching of the community moral values.